Faktor Pendukung Pendewasaaan Usia Perkawinan : Enabling Factors of Marriage Age Maturity - Wulan Angraini; Hilma Amrullah; Henni Febriawati; Riska Yanuarti (Poltekkes Kemenkes Palu, 2021)
Introduction: Maturity of age marriage (PUP) plays as an important role in implementation of population development and family planning programs that aimed in improving quality of life. The proportion of adolescents in Province Bengkulu who know about family development is still below national figure, which is only 61,67%. Purpose: it is known factor maturity age marriage in Province Bengkulu. Methods: Design research cross-sectional used secondary data from Performance Survey and Accountability Program (SKAP) in 2019. Research time July to December 2020. The research population who were successfully interviewed was 69,662 families. The sample research was coverage in Province Bengkulu were 341 people. Data analysis are univariable and bivariable chi-square. Results: 71.6% of adolescents in Bengkulu Province plan to get married when they are 21 years old for women and 25 years for men. Gender is factor enabling that influences maturity of age marriage (p-value=0.013 OR: 1,89 CI 95%: 1,16-3,07). Residence of adolescents (p-value=0.374) and wealth index of adolescents (p value=0.491) did not have a significant relationship with maturity of age marriage of adolescent in Bengkulu Province. Conclusion: Understanding of the ideal age for marriage needs to be give early as possible to prevent child marriage. Interventions related to maturity age marriage in rural areas need to be increased for adolescents through PLB which is an extension of the BKKBN.